Reliability Modeling of a System With One Main Unit and Two Associate Units Along With Sub-Unit - Saw, Hemant Kumar; Manker, H. L. (Communications in Mathematics and Applications, 2022)
In this paper, we develop a stochastic reliability model of a one-unit main system with two associate units. Each associate unit also has one sub-unit. Sub-units depend upon Associate units and associate units depend upon the main unit. The system will be operable when the main unit and at least one associate unit with sub-unit are in operation. As soon as a job arrives, all the units work with load. It is assumed that only one job is taken for processing at a time. There is a single repairman who repairs the failed units on a first-come-first-served basis. Various reliability characteristics of the system effectiveness will be obtained by using semi-Markov processes and regenerative point techniques.